2016
DOI: 10.1063/1.4954937
|View full text |Cite
|
Sign up to set email alerts
|

Computational and photoelectron spectroscopic study of the dipole-bound anions, indole(H2O)1,2−

Abstract: Articles you may be interested inPreparation and photoelectron spectrum of the glycine molecular anion: Assignment to a dipole-bound electron species with a high-dipole moment, non-zwitterionic form of the neutral core J. Chem. Phys. 120, 9899 (2004)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…DBSs have been suggested to play an important role as a gateway for anion formation 912. DBSs can be formed from neutral molecules by Rydberg electron transfer5,13 and have been investigated using photoelectron spectroscopy (PES) 14,15. Stable anions can have dipole-bound excited states near the electron detachment threshold if the neutral cores have large enough dipole moments 16,17.…”
Section: Introductionmentioning
confidence: 99%
“…DBSs have been suggested to play an important role as a gateway for anion formation 912. DBSs can be formed from neutral molecules by Rydberg electron transfer5,13 and have been investigated using photoelectron spectroscopy (PES) 14,15. Stable anions can have dipole-bound excited states near the electron detachment threshold if the neutral cores have large enough dipole moments 16,17.…”
Section: Introductionmentioning
confidence: 99%
“…Fermi and Teller first predicted a critical dipole moment of 1.625 D for a point dipole to bind an electron [7]. Many subsequent theoretical [8][9][10] and experimental [11,12] studies have shown that the practical minimum dipole moment is 2.5 D to form dipole-bound anions, which have been produced via Rydberg electron transfer (RET) [11][12][13] and electron attachment [14,15] and investigated by field detachment and photoelectron spectroscopy (PES). Stable anions with dipolar cores can possess excited DBSs just below the electron detachment threshold.…”
mentioning
confidence: 99%
“…Polar molecules can attract an excess electron, creating what is known as a dipole-bound anion [46]. As previously reported, NIPES has become an effective method to probe dipole bound state through observing spectroscopic signatures with strong and sharp peaks at a rather low EBE for species with sufficient dipole moment (>2.5 D) [46][47][48][49]. Our calculations from the B3LYP/6-31++G(d,p) level show that the APS • neutral has a dipole moment of 3.31 Debye which is significantly capable of supporting a DBS.…”
Section: Dipole-bound State (Dbs)mentioning
confidence: 99%